A review on potential of green solvents in hydrothermal liquefaction (HTL) of lignin. (November 2022) - Yiin, Chung Loong; Odita, Elatta bin; Mun Lock, Serene Sow; Cheah, Kin Wai; Chan, Yi Herng; Wong, Mee Kee; Chin, Bridgid Lai Fui; Quitain, Armando T.; Loh, Soh Kheang; Yusup, Suzana
Highlights: Highlighted the limitations of conventional biomass pretreatment methods. Discussed role of green solvents in extraction and HTL of lignin from biomass. Identified the most ideal process parameters for HTL of lignin. Reviewed the reaction mechanism and kinetic for HTL of lignin. Existing challenges of green solvents in HTL of lignin are emphasized. Graphical abstract: Abstract: One of the greatest challenges in biorefinery is to reduce biomass' recalcitrance and enable valorization of lignin into higher value compounds. Likewise, green solvents and hydrothermal liquefaction (HTL) with feasible economic viability, functionality, and environmental sustainability have been widely introduced in extraction and conversion of lignin. This review starts with the underscore of disadvantages and limitations of conventional pretreatment approaches and role of green solvents in lignin extraction. Subsequently, the effect of process parameters along with the reaction mechanisms and kinetics on conversion of lignin through HTL were comprehensively reviewed. The limitations of green solvents in extraction and HTL of lignin from biomass were discussed based on the current advancements of the field and future research scopes were also proposed. More details info on HTL of biomass derived lignin which avoid the energy-intensive drying procedures are crucial for the accelerated development and deployment of the advanced lignin biorefinery.